A reader for Nordic phoneticians. Kirsten Gregersen & Hans Basbøll (eds.): Nordic Prosody IV. Papers from a symposium. Odense University Studies in Linguistics Vol. 7. Odense: Odense University Press. 1986. 192 p. - Fant, Lars (HERMES - Journal of Language and Communication in Business, 1989)
No abstract.